The role of reflux time in a leach bed reactor coupled with a methanogenic reactor for anaerobic digestion of pig manure: Reactor performance and microbial community. (1st January 2020) - Yang, Jie; Wang, Dehan; Luo, Zifeng; Zeng, Weishen; Huang, Honghui
Abstract: A leach bed reactor coupled with a continuous stirred tank reactor (LBR-CSTR) is a set of clean production systems that can reduce pig manure (PM) pollution at the source. In this work, the VFA yield in LBR was increased, and then the methane yield was increased by investigating the role of the reflux time in the LBR-CSTR for anaerobic digestion of PM. With 2 reflux times per day, a significant impact on Proteobacteria was observed (the species had increased in abundance by the 6th day), and the methanogenic archaeal diversity increased by 27.08%, the highest methane yield of 167.6 mL/g volatile solids (VS) of PM and the highest solids reduction of 97.35% were obtained. The process improves both the reduction of piggery waste and the production of methane, making it a green and sustainable development process. Highlights: A set of clean production system that can reduce pig manure pollution at the source. The applicability of different reflux times in leach bed reactors is demonstrated. Improved both the waste reduction (97.35%) and the methane yield (167.6 mL/g). An inorganic filtration medium for mono-anaerobic digestion of pig manure is used.